Effect of the FreeStyle Libre™ flash glucose monitoring system on glycemic control in individuals with type 2 diabetes treated with basal–bolus insulin therapy: An open label, prospective, multicenter trial in Japan. Issue 1 (9th September 2020) - Ogawa, Wataru; Hirota, Yushi; Osonoi, Takeshi; Tosaki, Takahiro; Kato, Yoshiro; Utsunomiya, Kazunori; Nishimura, Rimei; Nakamura, Jiro
Abstract: Aims/Introduction: We investigated the effect of FreeStyle Libre TM on glycemic control in Japanese type 2 diabetes patients treated with basal–bolus insulin therapy. Materials and Methods: This prospective, 90‐day single‐arm study enrolled 94 adults with type 2 diabetes treated with insulin. A 14‐day masked baseline phase was followed by an 11‐week treatment phase during which participants used the device to monitor glucose levels. The primary end‐point was time spent in hypoglycemia (<70 mg/dL) for baseline versus study end (days 76–90). Secondary end‐points included other measures of glycemic control, along with patient satisfaction using the Japanese Diabetes Treatment and Satisfaction Questionnaire. Results: Time spent in hypoglycemia was low at baseline (0.51 ± 0.93 h/day) and did not significantly decrease at study end (0.47 ± 0.63 h/day, P = 0.6354). Time in range, time in hyperglycemia and estimated A1c all improved versus baseline (by +1.7 ± 3.0 h/day, −1.6 ± .4 h/day and −0.4 ± 0.8%, respectively, P < 0.0001 in each). Finger stick tests fell from 2.9 ± 1.3 to 1.9 ± 1.4/day, and mean scanning frequency during the intervention phase was 11.3/day. The mean treatment satisfaction score increased by 11.8 ± 5.3 ( P < 0.0001). Two severe hypoglycemia‐related adverse events were reported; one of which was possibly related to the device. Three participants reported mild device‐related skin trauma, site discomfort or subcutaneous bleeding. Conclusions: Use of FreeStyle Libre by Japanese type 2 patients diabetes treated with basal–bolus insulin therapy showed a low baseline of hypoglycemia, and enabled improved glycemic control and treatment satisfaction. Abstract : Use of flash glucose monitoring technology in Japanese subjects with type 2 diabetes, treated with multiple daily insulin injections, resulted in increased time in range and decreased time in hyperglycemia without increasing hypoglycemia.